1980
DOI: 10.1107/s0567739480001350
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoatom expansions of the H2 electron density

Abstract: Representations of a high-quality molecular electron density are studied. An evaluation of restricted radial functions is made using a least-squares figure of merit, the molecular quadrupole moment, the electric field at the nucleus, the electric-field gradient at the nucleus, an approximate energy and difference-density maps. It is concluded that for an accurate representation expansions to the quadrupole level or higher are needed with either single-term Slater-type radial functions having all exponents opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…If a further radial function is added to give a two-term expression, the power of r of the additional function is incremented by one. An earlier study on H2 (Chandler et al, 1980) found that both two-and three-term radial functions give very similar results, and so only single and two-term expansions are examined in the present paper.…”
Section: Pbk(rb) = ~ Pnk Nnk R~ Exp(--¢ N Rt ) (4) N=kmentioning
confidence: 88%
See 3 more Smart Citations
“…If a further radial function is added to give a two-term expression, the power of r of the additional function is incremented by one. An earlier study on H2 (Chandler et al, 1980) found that both two-and three-term radial functions give very similar results, and so only single and two-term expansions are examined in the present paper.…”
Section: Pbk(rb) = ~ Pnk Nnk R~ Exp(--¢ N Rt ) (4) N=kmentioning
confidence: 88%
“…The methods used are similar to those described in a previous paper (Chandler, Spackman & Varghese, 1980). For a diatomic molecule the calculated electron density is represented as the sum of two nuclearcentred multipole expansions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2.3) can be condensed in a single term if and only if the rank of matrix C, noted rank(C), is 1, i.e., if and only if the following condition is satisfied: for all i l , j l , i 2 , j 2 such that 1 s i l < i 2 5 1 and 1 5 j l < j 2 5 I' Cil,jlCiz,jz = C i j . j z C i 2 , j l ; (2)(3)(4) so, in this case, the wave function can be written in the form of a generalized HF function: @ = 9 , 4 9 5 .…”
Section: B Wave Functionmentioning
confidence: 99%